2015
DOI: 10.1007/s10533-015-0155-7
|View full text |Cite
|
Sign up to set email alerts
|

Classes of dissolved and particulate phosphorus compounds and their spatial distributions in the water of a eutrophic lake: a 31P NMR study

Abstract: Knowledge of phosphorus (P) components in water is vital to understanding the biogeochemistry of the P cycle, but little information is available about P, especially organic P components in water. We used solution 31 P nuclear magnetic resonance technology ( 31 P NMR) to characterize the classes of dissolved and particulate P compounds, as well as their spatial variation, in eutrophic Lake Taihu, Eastern China. Results showed that orthophosphate and monoesters were the dominant components in dissolved and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…Results from 31 P NMR analyses showed that Ortho-P was the dominant fraction (on average 49.15%) of all PP compound groups detected, which was in accordance with a previous report [ 28 ]. The peak of Ortho-P concentrations was found in May in the phytoplankton-dominated zone and lake center zone; this phenomenon demonstrated that the concentration of Ortho-P in these two zones was affected by phytoplankton-derived particulate matter.…”
Section: Discussionsupporting
confidence: 92%
“…Results from 31 P NMR analyses showed that Ortho-P was the dominant fraction (on average 49.15%) of all PP compound groups detected, which was in accordance with a previous report [ 28 ]. The peak of Ortho-P concentrations was found in May in the phytoplankton-dominated zone and lake center zone; this phenomenon demonstrated that the concentration of Ortho-P in these two zones was affected by phytoplankton-derived particulate matter.…”
Section: Discussionsupporting
confidence: 92%
“…This is not unexpected, as previous estimates have calculated ATP to be less than 2% of the DOP pool (Björkman et al 2018). While our observed pyroP signal includes contributions from polyP and nucleoP α classes, several other studies have found pyroP to account for the majority of phosphoanhydrides in marine particulate material (Paytan et al 2003), cellular cultures (Cade-Menun and Paytan 2010), sediment (Sundareshwar et al 2001), and freshwater particulate and dissolved P (Bai et al 2015). Furthermore, work by Blake et al (2005) has demonstrated the significance of pyrophosphatase and pyroP, the later sourced from triphosate nucleotides, in regulating the δ 18 O signature of P i in seawater.…”
Section: Phosphoanhydridessupporting
confidence: 79%
“…However, use of a highly alkaline solvent skewed the proportion of long‐chain polyphosphate to short‐chain (Table ), enhancing the terminal phosphoanhydride signal, and also promoted diester hydrolysis, enhancing the monoester signal (Table ). These findings may impact the overall dominance of the monoester class previously found (Paytan et al ; Read et al ; Bai et al ), as well as potential overestimation of pyrophosphates (Sundareshwar et al ; Paytan et al ). In response to this challenge, Read et al () and Bai et al () have grouped pyrophosphates and polyP contributions of each class (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…These findings may impact the overall dominance of the monoester class previously found (Paytan et al 2003;Read et al 2014;Bai et al 2015), as well as potential overestimation of pyrophosphates (Sundareshwar et al 2001;Paytan et al 2003). In response to this challenge, Read et al (2014) and Bai et al (2015) have grouped pyrophosphates and polyP contributions of each class (Fig. 6).…”
Section: Bell Et Almentioning
confidence: 90%